Early apoptosis real-time detection by label-free SERS based on externalized phosphatidylserine. Issue 14 (16th May 2016) - Zhou, Haibo; Wang, Qiqin; Yuan, Detian; Wang, Jinyong; Huang, Yang; Wu, Huihui; Jian, Jingyi; Yang, Danting; Huang, Ning; Haisch, Christoph; Jiang, Zhengjin; Chen, Shanze
Abstract : Early apoptosis real-time detection by label-free SERS based on externalized phosphatidylserine using in situ synthesized silver nanoparticles. Abstract : Apoptosis is a tightly regulated cellular process that plays an essential role in the development, aging, cancer biology, immune response, and pathogenesis of various diseases. Herein, we report a new SERS sensing strategy for in vitro sensitive detection of early apoptotic cells. The principle of this method is to in situ synthesize silver nanoparticles (AgNPs) on the phosphatidylserine (PS) of the apoptotic cell membrane during the early apoptosis, which enables distinguishing normal and apoptotic cells. The total assay time of the presented method is only 10 min, thus being faster, cheaper and simpler than current techniques for the detection of apoptosis. The intrinsic mechanism was verified by different approaches based on externalized phosphatidylserine. In addition, the detection process is real-time and label-free; i.e., the intrinsic SERS spectra from the cellular membrane are directly employed for apoptosis real-time detection, which avoids using additional chemical or biological reagents as external signal indicators. Therefore, our SERS approach may serve as a potentially practical tool for sensitive and real-time detection of early cell apoptosis, complementing the state-of-the-art strategies, e.g. flow cytometry. While further investigation is required to better understand the intrinsic mechanism of the in situ coating method, the current results may provide another choice for real-time detection of early apoptosis.